Teachers' Perceptions on School Leadership Practices and Their Effect on Organizational Behavior: Basis for Feedback Framework - Surio, Maricris P.; Jimenez, Edward C. (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aimed to determine the effect of school head leadership practices as perceived by teachers on their organizational behavior. The study are as follows: majority of school leader’s leadership practices were found outstanding based on their mission, vision, and goals, school culture, policies and procedures, organization and resources, teachers, programs and instruction, school-community relations, and information collection and decision making; dimensions of organizational behavior such as institutional identification, duty and responsibility, helpfulness, administrative contribution, sacrifice, communication and interaction, and personal and institutional development were found strongly agree; there was a significant relationship between school head’s leadership practices and organizational behavior, however, school head’s leadership practices did not show significant effect on teacher’s organizational behavior.; and a proposed feedback framework is recommended.